THE CORRELATION OF CARAPACE WIDTH – BODY WEIGHT, CONDITION FACTOR, AND ABUNDANCE OF SCYLLA SERRATA FORSSKÅL, 1775 IN EMBANKMENT LANE SILVOFISHERY DEVELOPMENT AREA OF MAROS DISTRICT - Yunus, Budiman; Suwarni (International Journal of Research -GRANTHAALAYAH, 2020)
The research aims to find out the correlation of carapace width – weight, condition factor and abundance of mangrove crab based on observation time and sex in the coastal waters of Maros district, South Sulawesi. This research provides information on the pattern of growth and chubbiness of mangrove crabs and its abundance in the coastal area of Maros district, South Sulawesi. The study was conducted from early February until the end of April 2019. Sampling was conducted on the coastal area of Kuri Lompo and estuary of Maros which is an integrated mangrove pond development (silvofishery). 213 mangrove crabs (120 male and 93 female) obtained from fishermen were measured. The coefficient b of male and female mangrove crabs in February and March were 3.3626 and 2.6674, respectively. In April, b value of male and female mangrove crab was 3.5965 and 2.6506, respectively. This relation shows the growth type for males is allometric-positive whereas for females is allometric-negative. In April also saw the same growth coefficient in the previous month allometric positive for males and allometric negative for females. In general, the condition factor of male mangrove crabs in February and March is greater than female mangrove crabs. While, in April the condition factor of female mangrove crab is greater than male mangrove crab. The nature of condition factor of mangrove crab represents the distribution of crab abundance in the embankment lane silvofishery development area of 0.015 ind./m2.